Analisis Peran Kepala Sekolah dalam Pelaksanaan Total Quality Management di Sekolah Dasar Negeri Bulukantil - Muna Fauziah (Universitas Sebelas Maret, 2021)
This study aims to analyze the role of the principal and describe the implementation of total quality management at the Bulukantil State Elementary School. The research uses a qualitative approach. The research subject is the principal of the Bulukantil State Elementary School, Surakarta, and Central Java. Research data obtained through interview techniques, observation, and questionnaires. The data validity technique uses triangulation. Analysis of research data using interactive analysis techniques. The stages of analysis are data reduction, data presentation, and verification/drawing conclusions. There are two research conclusions, namely the principal has played a role in various aspects of the implementation of total quality management, both the role of educators, managers, administrators, leaders, innovators, motivators, and supervisors with a percentage of 81.24% and the implementation of total quality management in Bulukantil State Elementary Schools. has gone well through the stages of planning, organizing, mobilizing, measuring, and monitoring. So, it can be concluded that the implementation of total quality management at the Bulukantil State Elementary School has been in accordance with the stages and is supported by the various roles of the principal in the school.